PENGARUH KOMPOSISI PUPUK N-ORGANIK TERHADAP PERTUMBUHAN DAN KUALITAS BEBERAPA AKSESI KATUK {Sauropus androgynus (L.) Merr.} ASAL BOGOR - Rahayu, Arifah; Maulana, Yudi; Rochman, Nur (JURNAL AGRONIDA, 2023)
Katuk is a vegetable and biopharmaceutical plant, so it needs to be cultivated using environmentally friendly fertilizers, to produce products that are free from chemical residues.  This study was aimed at assessing the agronomic performance of several accessions of katuk plants of Bogor origin at various compositions of N-organic fertilizer. A factorial completely randomized design with two factors was used. The first factor was katuk accessions consisting of Dramaga, Cinangneng1, Cinangneng2, and Katulampa.  The second factor was N fertilizer compositions consisting of 100% N-urea, 100% N-cow urine, 100% N-MSC, 75% N-urea + 25% N-cow urine, 75% N-urea + 25% N-MSC, 50% N-urea + 50% N-cow urine, 50% N-urea + 50% N-MSC, 25% N-urea + 75% N-cow urine, 25% N-urea + 75% N-MSC, 0% N-urea + 0% N-cow urine + 0% N-MSC. Results showed that Katulampa katuk plants had the highest number of leaves, number of leaflets, fresh weight, dry weight, nitrate content, and total dissolved solid content. N fertilizer compositions gave significant effects on all growth and production parameters excluding stem diameter and number of leaflets. The use of 75% Ua + 25% Kp fertilizer composition significantly increased plant height, number of leaves, number of buds, total bud length, fresh weight, dry weight, nitrate content, and total dissolved solid content. The best quality katuk plants with the highest chlorophyll, carotene, and vitamin C contents were shown by Dramaga accession treated with 50% Urea + 50% cow urine and 50% Urea + 50% MSC, respectively.